A Wideband Antenna Integrated into a Military Fabric for X-Band Satellite Communication - Chutchavong, Vanvisa; Aroonmitr, Pongsathorn; Rakluea, Paitoon; Jangjing, Thinnawat; Rakluea, Chawalit; Wongsin, Norakamon (My University, 2025)
The study examines a wideband antenna solution that combines military fabric integration with X-band satellite functionality. The proposed antenna, with dimensions of 40×40×0.565 mm3, is constructed using gabardine fabric with a herringbone twill (HBT) pattern with physical parameters of 0.395 mm thickness, relative permittivity of 1.8848, and dielectric loss tangent measuring 0.02611. Testing in an anechoic chamber shows excellent agreement between simulated and measured results, with the antenna operating from 7.25 - 12.28 GHz, corresponding to a fractional bandwidth of 50.89%, a measured peak gain of 6.49 dBi, while radiation patterns, return loss, and gain measurements validate its practical performance. Exploiting advancements in wearable electromagnetic systems and demonstrating seamless integration into military apparel, the proposed antenna establishes a robust solution viable for deployment in sophisticated defense communication infrastructures.
Keywords: military fabric; satellite communication; Wideband antenna; X-band